Regulatory incentives as a moderator of determinants for the adoption of Malaysian food safety system - Fernando, Yudi; Ng, Hooi Huang; Walters, Timothy (Emerald Group Publishing Limited, 2015)
Purpose– The purpose of this paper is to investigate the contribution of regulatory incentives offered by regulators as a moderator variable enhancing adoption of Malaysian food safety system (MeSTI).Design/methodology/approach – Structural equation modelling (SEM) with partial least square (PLS) was used to examine the determinants of MeSTI adoption in food industry. Findings– Responses to a questionnaire were collected from 89 firms, and statistical results confirmed that organizational factors (top management support and perceived technical competent) and scheme factors (perceived usefulness and perceived ease of use) have significant influence upon MeSTI adoption.While environment factors (perceived industry pressure and perceived government pressure) and expected factors (expected social legitimacy and expected economic competitiveness) did not have significant impact on MeSTI adoption. Regulatory incentives the government offered had no moderating effect on the relationships of the determinants studied. Practical implications– Although many companies remain unfamiliar or have limited knowledge of MeSTI, the respondents surveyed herein, which were small and medium enterprises (SMEs), argued that MeSTI was very helpful in controlling food safety standards in Malaysia.Government or non government regulatory agencies should promote and encourage food industry compliance with the Malaysian food safety certification.Governments also need to rethink and redesign current regulatory incentives offers to the food industry, which often have no direct impact on the companies’ business.Originality/value– Though many factors potentially could influence the industry to adopt a food safety scheme, the moderating effect of regulatory incentives is an interesting area to study in relationship to its potential effects to adopt food safety standards and practices.In some extent, this serves as a yardstick for measuring the impact of voluntary compliance and points to future directions for what should occur in the future.